Solve for t
t = \frac{5}{2} = 2\frac{1}{2} = 2.5
t = -\frac{5}{2} = -2\frac{1}{2} = -2.5
Share
Copied to clipboard
-16t^{2}+100=0
Swap sides so that all variable terms are on the left hand side.
-16t^{2}=-100
Subtract 100 from both sides. Anything subtracted from zero gives its negation.
t^{2}=\frac{-100}{-16}
Divide both sides by -16.
t^{2}=\frac{25}{4}
Reduce the fraction \frac{-100}{-16} to lowest terms by extracting and canceling out -4.
t=\frac{5}{2} t=-\frac{5}{2}
Take the square root of both sides of the equation.
-16t^{2}+100=0
Swap sides so that all variable terms are on the left hand side.
t=\frac{0±\sqrt{0^{2}-4\left(-16\right)\times 100}}{2\left(-16\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -16 for a, 0 for b, and 100 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
t=\frac{0±\sqrt{-4\left(-16\right)\times 100}}{2\left(-16\right)}
Square 0.
t=\frac{0±\sqrt{64\times 100}}{2\left(-16\right)}
Multiply -4 times -16.
t=\frac{0±\sqrt{6400}}{2\left(-16\right)}
Multiply 64 times 100.
t=\frac{0±80}{2\left(-16\right)}
Take the square root of 6400.
t=\frac{0±80}{-32}
Multiply 2 times -16.
t=-\frac{5}{2}
Now solve the equation t=\frac{0±80}{-32} when ± is plus. Reduce the fraction \frac{80}{-32} to lowest terms by extracting and canceling out 16.
t=\frac{5}{2}
Now solve the equation t=\frac{0±80}{-32} when ± is minus. Reduce the fraction \frac{-80}{-32} to lowest terms by extracting and canceling out 16.
t=-\frac{5}{2} t=\frac{5}{2}
The equation is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}